Early Holocene Inland Occupation in the Semiarid North of Chile. (2nd January 2016) - Escudero, Antonia; Davila, Cristian; Villela, Felipe; Troncoso, Andrés; Méndez, César; López, Patricio
Abstract : The human occupation of the Pacific Rim of the southern Andes during the Pleistocene–Holocene transition was concentrated near the coast. The Pichasquita rockshelter in the Semiarid North of Chile, however, shows evidence of an early Holocene occupation of the inland mountains. This rockshelter functioned as a residential camp from which local fauna was exploited and vegetal resources were processed. Current information suggests early coastal groups extended their mobility circuits inland after 11, 000 cal yr BP.